2009
DOI: 10.1063/1.3180708
|View full text |Cite
|
Sign up to set email alerts
|

Transition from ferromagnetism to diamagnetism in undoped ZnO thin films

Abstract: We report a systematic study of the film thickness dependence (0.1–1 μm) of room-temperature ferromagnetism in pure magnetron-sputtered ZnO thin films wherein a sequential transition from ferromagnetism to paramagnetism and diamagnetism as a function of film thickness is observed. The highest saturation magnetization (MS) value observed is 0.62 emu/g (0.018 μB/unit cell) for a ∼480 nm film. On doping the ZnO film with 1 at. % Mn enhances the MS value by 26%. The ferromagnetic order in ZnO matrix is believed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 20 publications
2
51
2
Order By: Relevance
“…Theoretically, Dietl et al first predicted that p-type Mn doped ZnO would show ferromagnetism with T C well above RT [3]. In contrast, Co-doped ZnO was theoretically predicated to become ferromagnetic with n-type doping [4] and a flood of experimental studies of this subject have been reported upon [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the presented data were plagued by instability and a lack of reproducibility.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Theoretically, Dietl et al first predicted that p-type Mn doped ZnO would show ferromagnetism with T C well above RT [3]. In contrast, Co-doped ZnO was theoretically predicated to become ferromagnetic with n-type doping [4] and a flood of experimental studies of this subject have been reported upon [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the presented data were plagued by instability and a lack of reproducibility.…”
Section: Introductioncontrasting
confidence: 56%
“…Additionally, it is surprising that several groups observed distinct ferromagnetic signals in ZnO thin films and nano-particles without TM doping [16,17], and it seems that the charge-transfer ferromagnetism model can give a satisfactory explanation for them [18]. However, in all the above cases, they are not true DMSs.…”
Section: Introductionmentioning
confidence: 84%
“…From this value, we can estimate that the size of the particles forming the film is less than 30 nm. Recently, Kapilashrami et al 19 used the same technique (cross-section) to determine the thickness of ZnO films measuring between ca. 150 and 1000 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Recently room temperature ferromagnetism (RTFM) has been widely reported in undoped oxides, such as ZnO [12,13], HfO 2 [14], TiO 2 [15], SnO 2 and In 2 O 3 [16] containing no transition metal doping. This so-called d 0 ferromagnetism has challenged our understanding of the origin of ferromagnetism in these undoped oxides.…”
Section: Introductionmentioning
confidence: 99%